GAS6/Axl Signaling Modulates Blood-Brain Barrier Function Following Intravenous Thrombolysis in Acute Ischemic Stroke - Guo, Zhen-Ni; Liu, Jie; Chang, Junlei; Zhang, Peng; Jin, Hang; Sun, Xin; Yang, Yi (Frontiers in Immunology, 2021)
Background and Purpose: Recent studies have shown that several proteins, including Axl, are related to hemorrhagic transformation (HT) following intravenous thrombolysis by affecting blood-brain barrier (BBB) function. However, the effects of these proteins on BBB function have been studied primarily in animal models. In this study, we aimed to identify serum protein markers that predict HT following intravenous thrombolysis in patients with acute ischemic stroke (AIS) and verify whether these serum proteins regulate BBB function and HT in animal stroke models. Methods: First, 118 AIS patients were enrolled in this study, including 52 HT patients and 66 non-HT patients. In Step 1, baseline serum levels of Axl, angiopoietin-like 4, C-reactive protein, ferritin, hypoxia-inducible factor-1 alpha, HTRA2, Lipocalin2, matrix metallopeptidase 9, platelet-derived growth factor-BB, and tumor necrosis factor alpha were measured using a quantitative cytokine chip. Next, sequence mutations and variations in genes encoding the differentially expressed proteins identified in Step 1 and subsequent function-related proteins were detected. Finally, we verified whether manipulation of differentially expressed proteins affected BBB function and HT in a hyperglycemia-induced rat stroke model. Results: Serum Axl levels were significantly lower in the HT group than in the non-HT group; none of the other protein markers differed significantly between the two groups. Genetic testing revealed that sequence variations of GAS6 (the gene encoding the Axl ligand)-derived long non-coding RNA, GAS6-AS1, were significantly correlated with an increased risk of HT after intravenous thrombolysis. In animal studies, administration of recombinant GAS6 significantly reduced brain infarction and neurological deficits and attenuated BBB disruption and HT. Conclusions: Lower serum Axl levels, which may result from sequence variations in GAS6-AS1, are correlated with an increased risk of HT after intravenous thrombolysis in stroke patients. Activation of the Axl signaling pathway by the GAS6 protein may serve as a therapeutic strategy to reduce HT in AIS patients.